ANALYSIS OF CAPITAL SOURCES AND BUSINESS CAPITAL MANAGEMENT IN UMKM PASTRIES TO MAK NI NORTH ACEH - Marbawi; Lisa Dwi Yana; Nailul Authar; Hervina Hervina; Salsabila Salsabila (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The purpose of this study is to find out and analysis where and how the source of capital and the management of business capital by Umkm.the object of this study is Umkm in makni. This research uses the technique of Participation Observation, and formal interviews as for the results of this study are Umkm get a source of capital from business accelerator cooperation with PT. Global energy development (PGE), and the way capital management is carried out in the form of business diversification activities which is also one of the ways of developing MSME businesses towards mak ni.